Acute blood loss during burn and soft tissue excisions: An observational study of blood product resuscitation practices and focused review. (June 2015) - Pidcoke, Heather F.; Isbell, Claire L.; Herzig, Maryanne C.; Fedyk, Chriselda G.; Schaffer, Beverly S.; Chung, Kevin K.; White, Christopher E.; Wolf, Steven E.; Wade, Charles E.; Cap, Andrew P.
Abstract : BACKGROUND: Many military and civilian centers have shifted to a damage-control resuscitation approach, focused on providing oxygen-carrying capacity while simultaneously mitigating coagulopathy with a balanced ratio of platelets and plasma to red blood cells. It is unclear to what degree this strategy is used during burn or soft tissue excision. Here, we characterized blood product transfusion during burn and soft tissue surgery and reviewed the published literature regarding intraoperative coagulation changes. We hypothesized that blood product resuscitation during burn and soft tissue excision is not hemostatic and would be insufficient to address hemorrhage-induced coagulopathy. METHODS: Consented adult patients were enrolled into an institutional review board–approved prospective observational study. Number, component type, volume, and age of the blood products transfused were recorded during burn excision/grafting or soft tissue debridement. Component bags (packed red blood cells, fresh frozen plasma, platelets, and cryoprecipitate) were collected, and the remaining sample was harvested from the bag and tubing. Aliquots of 1/1, 000th the original volume of each blood product were obtained and combined, producing an amalgam sample containing the same ratio of product transfused. Platelet count, rotational thromboelastometry, and impedance aggregometry were measured. Significance was set at p < 0.05. RESULTS: Amalgamated transfusate samples produced abnormally weak clots ( p ⩽ 0.001) particularly if they did not contain platelets. Clot strength (48.8 [2.6] mm; reference range, 49–71 mm) for platelet-containing amalgams was below the lower limit of the reference range despite platelet–red blood cell ratios greater than 1:1. Platelet aggregation was abnormally low; transfused platelets were functionally inferior to native platelets. CONCLUSION: Our study and focused review demonstrate that further work is needed to fully understand the needs of patients undergoing tissue excision. The three studies reviewed and the results of our observational work suggest that coagulopathy and thrombocytopenia may contribute to intraoperative hemorrhage. Blood product resuscitation during burn and soft tissue excision is not hemostatic. LEVEL OF EVIDENCE: Epidemiologic study, level V.